Associations between the consumption of carbonated beverages and periodontal disease: The 2008–2010 Korea national health and nutrition examination survey. Issue 28 (July 2016) - Song, In-Seok; Han, Kyungdo; Ko, Youngkyung; Park, Yong-Gyu; Ryu, Jae-Jun; Park, Jun-Beom
Abstract : Abstract: Consumption of carbonated beverages was reported to be associated with obesity and other adverse health consequences. This study was performed to assess the relationship between the consumption of carbonated beverages and periodontal disease using nationally representative data. The data from the Korea National Health and Nutrition Examination Survey conducted between 2008 and 2010 were used; the analysis in this study was confined to a total of 5517 respondents >19 years old who had no missing values for the consumption of carbonated beverages or outcome variables. The community periodontal index greater than or equal to code 3 was defined as periodontal disease. The odds ratios of the percentage of individuals with periodontal treatment needs tended to increase with the consumption of carbonated beverages. Adjusted odds ratios and their 95% confidence intervals adjusted for various factors including age, sex, body mass index, smoking, drinking, exercise, metabolic syndrome, frequency of tooth brushing per day, use of secondary oral products, dental checkup within a year, consumption of coffee of the individuals with the consumption of carbonated beverages once or less per month, once or less per week and twice or more per week were 1.109(0.804, 1.528), 1.404(1.035, 1.906), and 1.466(1.059, 2.029), respectively. A subgroup analysis revealed that in individuals with body mass index < 25 or waist circumference < 90 cm for males or < 80 cm for females, the prevalence of periodontal disease increased with higher consumption of carbonated beverages ( P for trend < 0.05). Consumption of carbonated beverages was positively associated with the risk of periodontal disease in Korean adults. In a subgroup analysis, the individuals consuming carbonated beverages with body mass index < 25 or waist circumference < 90 cm for males or < 80 cm for females were more likely to have periodontal disease. Consumption of carbonated beverages may be considered to be an independent risk indicator for periodontal disease and periodontal health of nonobese individuals may benefit from reduction of carbonated beverage consumption.